Expression of survival and apoptotic molecules in response to early stage chemotherapy in acute myeloid leukaemia - Yiau, Stephnie Kang Xian (2013)
Acute myeloid leukaemia (AML) is a haematological malignancy characterised by a predominance of myeloid precursor cells that leads to death if not treated. A major factor in the failure of AML chemotherapy is due to the acquisition of multidrug resistance (MDR) by the malignant myeloblast. Factors such as cytokines, activation of signalling pathway mediators and Bcl-2 family proteins contributes to cell survival, thus leading to MDR. Bone marrow aspirate was collected a month after induction therapy to determine complete remission (CR). It is postulated that the treatment outcome could be determined during early induction therapy through the expression pattern of cellular molecules in peripheral blood. The expression patterns of stem cell marker, CD34, c-Kit receptor (CD117), cytokines and their receptors, signalling mediators of the PI3K/Akt and MAP kinase pathway, and Bcl-2 family proteins were observed in the peripheral blood of AML patients collected before and/or during Day 3 of induction therapy with anthracycline and cytarabine arabinoside (Ara-C). Expression were measured using flow cytometry for the percentage of cells expressing and geometric mean fluorescent intensity (MFI), as well asRT-PCR. Results showed that the percentage of cells expressing IL-1β (p=0.028), the MFI of IL-18Rα (p=0.01), MFI ( p=0.007) and mRNA levels (p=0.038) of TNF-α, MFI of DR5 (p=0.02) and MFI of pAkt-T308 (p=0.038) was found to be significantly higher in samples of sensitive patients prior to induction therapy. Untreated resistant samples were found to have significantly higher MFI for pFKHR (p=0.05). During induction therapy, we found that in sensitive samples,IL-18Rα was found to be significantly higher in the percentage of expressing cells (p=0.014) and the MFI (p=0.02)was higher as well. These treated sensitive samples were also found to have significantly higher pp38 MFI (p=0.039). Treated resistant samples were found to have significantly higher percentage of CD34 (p=0.028) and pBAD (p=0.014) expressing cells. Spearman Rank-order correlation analysis showed that there is no correlation between the MFI and the mRNA transcript of cytokine and its receptors. Similar correlations analysis were also observed between cytokines and receptors with signalling mediators and apoptotic molecules, pBAD and Bim. Some of these correlations corresponded to the cytokines role in apoptosis and survival but there are some contradictions. Molecules such as DR5, CD34, pFKHR and pBAD are potential prognostic markers of treatment outcome but some might not be suitable markers of treatment outcome at the early stages of induction therapy.